Design and Investigation of a Semi-Partitioned Bioreactor for Extractive Fermentation using Computational Fluid Dynamics simulations and experimental studies - Teke, George Mbella (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.